Correlation Study Between Soil Moisture and Land Use Based On Satelite Imaging (Study Case Bandung and Its Surrounding) - FARDANI (NIM 12803011); Pembimbing: Dra. Sri Hartati Soenarmo, MSP., IRLAND
Soil moisture is an important factor for life and is very interesting to study. The main function of soil moisture is to distribute rain water that precipate to be 'run off' or infiltration. Soil moisture is very important to water potentional study and water balance study. This observation used two data wich are : aster satellite image for bandung at 12 june 2003 and soil moisture data from field measurement. The data was used to study the correlation between soil moisture and land use. In this observation, soil moisture was approach by two inputs which is : Natural Difference Vegetation Index (NDVI) which is vegetation figure data on the land surface and Natural Difference Temperature Index (NDTI), which is surface temperature figure data. From Non Parametric Spearman Rank test result, the rank between soil moisture and land uses pixel value showed there was no correlation among 3 land use types, which are forest with measured rho -0.6, garden with measured rho 0.057 and settlement with measured rho 0.30 because the value didn't comply with table limit rho value. However agricultural field with measured rho -0.718 fulfilled the table rho value for significance level of 5%, which is 0.648.,so agricultural filed has a good correlation with soil moisture because filed data was spread on agricultural land use, so there is a correlation between agricultural filed land use and soil moisture.